Influence of Halal Certification on Innovation and Financial Performance - Dekar Urumsah; Dyah Ayu Puspitasari (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This research is to empirically examine the influence of halal certification on innovation and financial performance by adopting Resource Based View (RBV) theory. The data used were the financial statements of food and beverage corporates listed at Indonesian Stock Exchange of 2015-2018 period. The analysis method employed was multiple linear regression using SPSS. The results show that halal certification significantly and positively affects financial performance. Similarly, innovation also results in positive and significant effect on financial performance, and halal certification positively and significantly affects innovation and financial performance. A number of implications are catered by this research, such as theoretical contribution toward the existing literature related to food corporations in Indonesia. This is expected to be a reference for the study on halal food corporation in Indonesia, as well as to provide knowledge of the improvement of financial performance and innovation through halal certification for food corporate management. performance and innovation through halal certification for food corporate management.